Resting metabolic rate and body composition in 386 Japanese young male athletes - Fukuda, R.; Tahara, Y. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Resting metabolic rate (RMR) represents the largest fraction of individual`s daily energy expenditure, accounting for about 60 75% of an individual`s total daily energy expenditure. A variety of factors , especially a fat-free mass (FFM), have been shown to influence RMR. Many studies, therefore, have examined regarding the effects of physical exercise induced increase FFM, on RMR. Little was known about the level of RMR in athletes, however. PURPOSE: The purpose of this study was to measure RMR in male Athletes of Senior High School and Adult and to examine relationships between RMR and body composition METHODS: Three hundred sixteen eight male athletes who were top-level athletes of Nagasaki prefecture in Japan, participated in the study, including 114 longdistance runners (mean age 21.6±4.0 years), 103 football players (mean age 17.3±1.0 years), 8 volleyball players (mean age 16.6±0.4 years), 56 canoeists (mean age 21.6±4.0 years), 21 swimmers (mean age 15.9±1.2 years), 48 cyclists ( mean age 16.8±0.8 years) and 28 rugby football players (mean age 20.0±3.6 years). Oxygen consumption (VO2) was measured via open circuit indirect calorimetry using the classical Douglas bag method for measurement RMR (kJ/hr.) after at least 30 minutes of resting on the chair. Body density was measured by the under-water weighing method, and Brozek`s equation was applied to calculate percentage body fat (%fat, %) and fatfree mass (FFM, kg). The measurement started more than 3 hours after the previous meal. RESULTS : For all subjects, the mean (±SD) body weight (BW, kg), height(cm), body surface area (BSA, m2), FFM and RMR were 62.3±7.6kg, 171.2±4.9cm, 1.68±0.11m2, 56.1±6.1kg, and 311.7±40.2 (kJ/hr.), respectively. RMR for each event were 359.0±39.9 in rugby football players, 321.4±28.8 in swimmers, 316.8±43.6 in cyclists, 315.3±40.8 in canoeists, 311.1±30.8 in football players, 303.1±36.5 in volleyball players and 294.4±34.5 in longdistance runners, respectively. RMR of rugby football players were significantly higher than any other events. Whereas, swimmers had higher mean values of RMR/BW (kJ/kg/hr.), RMR/FFM (kJ/kg/hr.) and RMR/BSA (kJ/m2/hr.) than players of other events. RMR showed correlation coefficient of 0.536 with Weight (p < 0.001), 0.526 with BSA (p < 0.001) and 0.517 with FFM(p < 0.001). CONCLUSION : When RMR was expressed in either kJ/ hr., kJ/kg BW/hr., kJ/kg FFM/hr. or kJ/BSA m2/hr., there was a significant difference between the sporting events.